1994
DOI: 10.1111/j.1550-7408.1994.tb01509.x
|View full text |Cite
|
Sign up to set email alerts
|

A Tandem Repeat of Rat‐derived Pneumocystis carinii Genes Encoding the Major Surface Glycoprotein

Abstract: A fragment from the genome of rat-derived Pneumocystis carinii was found to contain two MSG genes arranged as a direct repeat. The sequences from one gene (MSG B), the region between the two genes, and part of the second gene (MSG A) were determined. The two MSG genes were not identical in sequence. The open reading frames of MSG A and MSG B encode non-identical proteins, both of which are similar to that encoded by a previously published cDNA. The MSG B gene sequence showed no evidence of introns. The 5' and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 42 publications
3
64
0
Order By: Relevance
“…Gigliotti et al (18), using immunoelectron microscopy, demonstrated that MSG is distributed on the surface of all developmental stages of P. carinji. Through molecular studies of rat and ferret P. carindi, it has been demonstrated that MSG represents a group of proteins encoded by multiple genes (6)(7)(8)19). Numerous unique MSG cDNAs have been identified, establishing that multiple mRNAs are transcribed within a population of organisms (6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gigliotti et al (18), using immunoelectron microscopy, demonstrated that MSG is distributed on the surface of all developmental stages of P. carinji. Through molecular studies of rat and ferret P. carindi, it has been demonstrated that MSG represents a group of proteins encoded by multiple genes (6)(7)(8)19). Numerous unique MSG cDNAs have been identified, establishing that multiple mRNAs are transcribed within a population of organisms (6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…With the recent progress in cloning and expressing MSG genes (6)(7)(8)(9), it should be possible to develop T cell clones, map their epitopes, and test their functional importance in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A P. carinii genomic library was constructed in lgt11 by standard methods (Sambrook et al, 1989;Linke et al, 1998). Approximately 3x10 6 plaques were screened with the RA-C11 mAb, and positive plaques were isolated as described previously (Sunkin et al, 1994;Garbe & Stringer 1994;Schaffzin, 1999). For analysis of proteins encoded by a lgt11 clone, crude lysates were generated from bacteria (Escherichia coli Y1090r 2 ) lysogenic for the phage (Sambrook et al, 1989).…”
Section: Methodsmentioning
confidence: 99%
“…carinii organisms express a surface antigen known as the major surface glycoprotein (MSG) (Walzer & Linke, 1987;Kovacs et al, 1988;Tanabe et al, 1989;Nakamura, 1998;. Multiple forms of MSG are encoded by a family of approximately 100 genes, members of which are located at 34 telomeric sites (Stringer et al, 1991;Kovacs et al, 1993;Sunkin et al, 1994;Sunkin & Stringer, 1996, 1997Cornillot et al, 2002;Keely et al, 2003). Other species of Pneumocystis, including the species that infects humans, also have families of MSG genes (Haidaris et al, 1991;Stringer et al, 1993;Garbe & Stringer, 1994;Wright et al, 1995;Mei et al, 1998;Haidaris et al, 1998;Schaffzin et al, 1999;Kutty et al, 2001).…”
Section: Introductionmentioning
confidence: 99%